EFEKTIVITAS YOGA TERHADAP NYERI DISMENORE PADA REMAJA - Melda Friska Manurung; Sri ' Utami; Siti Rahmalia HD ' Rahmalia HD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Dysmenorrhea is increasing and excessive pain during menstruation. There is some pain management to overcome the pain of dysmenorrhea, one of which is with yoga. This study aims to determine the effectiveness of yoga to decrease the intensity of dysmenorrhea pain. The design of this research study "Quasy experiment" using "non-equivalent kontrol group" which is divided into an experimental group and a control group. The study was conducted at SMK Negeri 7 Pekanbaru, the number of 30 students were taken using simple random sampling technique. Measuring instruments used are observasi.Tindakan sheet was conducted for 45 minutes 3x to rest 5 minutes each treatment. The analysis used univariate and bivariate analysis using the Mann Whitney and Wilcoxon. The study found a decrease in the intensity of dysmenorrhea pain in the experimental group after given yoga (p value 0,000 < α 0,05) The results of this study that merekomdasikan yoga can be used for young women, especially women who have dysmenorrhea to reduce the intensity of pain dysmenorrhoea.